Immune tolerance against HBV can be overcome in HBV transgenic mice by immunization with dendritic cells pulsed by HBVsvp - Farag, Mohamed Mansour Saad; Flechtenmacher, Christa; Stremmel, Wolfgang (Vaccine, 2012)
In chronic Hepatitis B Virus (HBV) infection the function of dendritic cells (DC), T- and B-cells is impaired. DC vaccination is an option to overcome this. DC pulsed in vitro with HBV sub viral particles (HBVsvp) and used to immunize mice can activate HBV directed humoral and cellular immune responses. In the present study we vaccinated HBV transgenic mice as a model for chronic HBV infection and observed humoral and cellular immune responses. In these mice, the lacking immune response against HBV is mainly due to peripheral tolerance. HBVsvp, together with LPS as a co-activating molecule, were used for pulsing and in vitro activation of DC. HBV transgenic mice were injected with pulsed DC two times. Four weeks after DC vaccination humoral and cellular immune responses, viral antigen levels and liver histology were analyzed. DC vaccinated HBV-transgenic mice developed a strong HBV specific antibody and T-cell response after DC vaccination. Neither circulating HBV antigen levels nor viremia, however, were controlled. No liver damage was observed. These results demonstrate that in vitro activation of DC and loading with HBVsvp can overcome tolerance against HBV and reactivate B- and T-cell responses in HBV transgenic mice, but were not sufficient to lead to virus control in these mice. Vaccination using DC, the key players of cellular and humoral immunity, after in vitro reactivation promises to break tolerance against HBV and may help patients with chronic hepatitis B to clear the infection.